2020
DOI: 10.1021/acsami.0c14624
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight Selective Photodeposition of CoOx(OH)y and NiOx(OH)y on Truncated Bipyramidal BiVO4 for Highly Efficient Photocatalysis

Abstract: Facet-engineered monoclinic scheelite BiVO4 particles decorated with various co-catalysts were successfully synthesized by selective sun light photodeposition of metal or metal oxy(hydroxide) nanoparticles onto the facets of truncated bipyramidal BiVO4 monoclinic crystals co-exposing {010} and {110} facets. X-ray photoelectron spectroscopy, scanning electron microscopy and scanning Auger microscopy revealed that metallic silver (Ag) and cobalt (oxy)hydroxide (CoOx(OH)y) particles were selectively deposited ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 78 publications
2
12
0
Order By: Relevance
“…The O 2 evolution rate for the 3DOM BiVO 4 is ∼660 μmol h –1 g –1 (for 0.05 g of photocatalyst), which is on par with the best performing BiVO 4 photocatalyst (Table S1). Furthermore, the 3DOM BiVO 4 sample exhibits a higher anodic photocurrent density than the platelike BiVO 4 (Figure b), which also agrees well with the trend of photocatalytic gas evolution activities. Interestingly, a more negative onset potential and a sharper increase of photocurrent density between 0.4 and 0.6 V versus reversible hydrogen electrode (RHE) were observed for the 3DOM BiVO 4 , which is possibly ascribed to their different surface work functions .…”
supporting
confidence: 77%
“…The O 2 evolution rate for the 3DOM BiVO 4 is ∼660 μmol h –1 g –1 (for 0.05 g of photocatalyst), which is on par with the best performing BiVO 4 photocatalyst (Table S1). Furthermore, the 3DOM BiVO 4 sample exhibits a higher anodic photocurrent density than the platelike BiVO 4 (Figure b), which also agrees well with the trend of photocatalytic gas evolution activities. Interestingly, a more negative onset potential and a sharper increase of photocurrent density between 0.4 and 0.6 V versus reversible hydrogen electrode (RHE) were observed for the 3DOM BiVO 4 , which is possibly ascribed to their different surface work functions .…”
supporting
confidence: 77%
“…According to the elemental composition, these reduction cocatalysts can be further classified as elemental metals (e.g., Ni, [ 29 ] Cu, [18b] and CoNi alloy [ 30 ] ), metal sulfides (e.g., MoS 2 , [ 31 ] NiS, [ 32 ] and CoMoS x [ 33 ] ), metal phosphides (e.g., Ni 2 P, [ 34 ] CoP, [ 35 ] and NiFeP [ 36 ] ), metal nitrides (e.g., Ni 3 N [24a] and Co 3 N [ 37 ] ), metal carbides (e.g., Ni 3 C [ 38 ] and Mo 2 C [ 39 ] ), metal borides (e.g., NiB [ 40 ] and NiCoB [ 41 ] ), metal oxides (e.g., NiO [ 42 ] and CuO [ 43 ] ), and metal hydroxides (e.g., Ni(OH) 2 [ 44 ] and Cu(OH) 2 [ 45 ] ) (Figure 1). In comparison, a few transition‐metal‐based cocatalysts are utilized as oxidation cocatalysts, involving the metals (e.g., Co [ 46 ] and Mn [ 47 ] ), oxides (e.g., CoO x [ 48 ] and MnO x [ 49 ] ), hydroxides (e.g., Co(OH) 2 [ 50 ] and Fe(OH) 3 [ 51 ] ), oxyhydroxides (e.g., FeOOH [ 52 ] and CoOOH [ 53 ] ), and phosphates (e.g., Co‐Pi [ 54 ] and CoNi‐Pi [27b] ), also as shown in Figure 1.…”
Section: Fundamentals Of Transition‐metal‐based Cocatalysts For Photo...mentioning
confidence: 99%
“…Transition metal hydroxides and oxyhydroxides have strong adsorption and hydrogen bonding interactions toward water molecules, therefore they could be utilized as promising oxidation cocatalysts on semiconductor photocatalysts to improve the photocatalytic water splitting performance. [ 388 ] Up to now, a few metal hydroxides such as cobalt hydroxide, [ 50,371 ] nickel hydroxide, [ 388 ] iron hydroxide, [ 51 ] and bimetal layered hydroxides [ 372–374 ] as well as some metal oxyhydroxides including iron oxyhydroxide, [21a,52,376,389] cobalt oxyhydroxide, [21b,21c,53,375] and nickel oxyhydroxide [ 53 ] have been investigated as cocatalysts for photocatalytic water oxidation. Since these hydroxides and oxyhydroxides have semiconducting properties, when they are supported on the surface of semiconductors, heterojunctions are inclined to be formed to accelerate the separation and transfer of photoinduced holes.…”
Section: Transition‐metal‐based Oxidation Cocatalysts For Photocataly...mentioning
confidence: 99%
See 1 more Smart Citation
“…are inclined to capture holes, while reduction cocatalysts, containing Ag, Au, Pt, etc., exhibit appetency for electrons. At the same time, the existence of cocatalysts is conducive to accelerate the spatial reaction for the redox process. Therefore, different cocatalysts can be reasonably designed to achieve the purposes of oxidation and reduction, respectively. Chung et al adopted a hydrothermal method to synthesize Pt-containing TiO 2 samples that demonstrated excellent hydrogen production performance and stability, and Liu and co-workers deposited CoFe-H on BiVO 4 photoanodes which displayed markedly heightened OER kinetics and photocurrent density .…”
Section: Introductionmentioning
confidence: 99%